Wind Erosion Control Technique - Thiruvenkataswamy, K.R. (Journal of Soil and Water Conservation, 2022)
Wind erosion is a serious menace in the 'eastern parts of Triunelveli district of Tamilnadu. Shelterbelts are raised to control the force of wind in order to reclaim • the tract rendered barren. Some experiments were carried out to evaluate the comparative rate of growth of a few tree species with reference to the rainfall received, the role of wind velocity on the growth, the period of actual growth of some species in a year, morphological changes of some species in the shelterbelts, the best soil for raising shelterbelt and the effect of protection on the growth of shelterbelt. The results are discussed in this paper. This will help in scientific planning and execution of the projects.